2010
DOI: 10.4049/jimmunol.1001709
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T Cells Are Not Required for the Induction of Dengue Virus-Specific CD8+ T Cell or Antibody Responses but Contribute to Protection after Vaccination

Abstract: The contribution of T cells to the host response to dengue virus (DENV) infection is not well understood. We previously demonstrated a protective role for CD8+ T cells during primary DENV infection using a mouse-passaged DENV strain and IFN-α/βR−/− C57BL/6 mice, which are susceptible to DENV infection. In this study, we examine the role of CD4+ T cells during primary DENV infection. Four I-Ab–restricted epitopes derived from three of the nonstructural DENV proteins were identified. CD4+ T cells expanded and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
141
2
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 176 publications
(155 citation statements)
references
References 69 publications
8
141
2
4
Order By: Relevance
“…Notably, however, a few studies have shown that HCMVspecific CD4 T cells can mediate killing directly ex vivo in cell culture assays (24)(25)(26). CD4 cytotoxic T lymphocytes (CTLs) can be induced in virus-infected mice within a relatively short time (weeks) (27)(28)(29)(30)(31)(32), albeit ex vivo assays have normally been used to define their killing capacity and human CD4 CTLs have been isolated and studied largely from persons who have been chronically infected for several years. Studies in both mice and humans suggest that perforin and granzyme are key mediators of CD4 T cellcytolytic activity, but tumor necrosis factor (TNF) family ligands, such as FasL and TRAIL, likely can also contribute (24,25,27,29,32).…”
mentioning
confidence: 99%
“…Notably, however, a few studies have shown that HCMVspecific CD4 T cells can mediate killing directly ex vivo in cell culture assays (24)(25)(26). CD4 cytotoxic T lymphocytes (CTLs) can be induced in virus-infected mice within a relatively short time (weeks) (27)(28)(29)(30)(31)(32), albeit ex vivo assays have normally been used to define their killing capacity and human CD4 CTLs have been isolated and studied largely from persons who have been chronically infected for several years. Studies in both mice and humans suggest that perforin and granzyme are key mediators of CD4 T cellcytolytic activity, but tumor necrosis factor (TNF) family ligands, such as FasL and TRAIL, likely can also contribute (24,25,27,29,32).…”
mentioning
confidence: 99%
“…In both the A129 and AG129 mice, DENV was cleared between days 4 and 6 postinfection at approximately the same rate in all tissues examined, with the exception of the CNS. This suggests that extraneural clearance is independent of IFN-␥R, although it is dependent on CD8 ϩ T cells (48,50). However, A129 mice, but not AG129 mice, clear DENV from the brain in an IFN-␥R-dependent manner.…”
Section: Discussionmentioning
confidence: 91%
“…Perhaps DENV's extreme susceptibility to the murine type I IFN-signaling pathway (33,34), the molecules of which differ sufficiently from human analogues to prevent DENV-mediated inhibition (3), limits extraneural antigen availability and results in a blunted cellular immune response. Accordingly, we have observed that the breadth and magnitude of DENV-specific T cell responses in wild-type mice are lower than in IFN-␣/␤ receptor-deficient mice (45,48,50). Combined with the immune-privileged status of the CNS and the capacity of DENV for infection of the CNS, a blunted T cell response may favor efficient DENV replication in the CNS.…”
Section: Discussionmentioning
confidence: 96%
“…It has also been shown that interferon is one of three major barriers that limit poliovirus trafficking from the periphery to the central nervous system (CNS), and knocking out part of the interferon response allowed a greater portion of the viral population to enter the brain (30). Interferon deficiency of AG129 mice aids in the systemic spread of viral infections (31,32) while maintaining humoral and cell-mediated immunity (33)(34)(35). In our model, eliminating interferon allowed the virus to spread to more organs, including the brain.…”
Section: Figmentioning
confidence: 99%